?EFFECT OF PRE-PLANT INCORPORATED AND POST-EMERGENCE HERBICIDES ON GROWTH AND YIELD OF SUNFLOWER (Helianthus annuus L.) (Biological Sciences - PJSIR, 1996)
A field experiment was conducted to study the effect of pre-plant incorporated and post-emergence herbicides on the growth and yield of sunflower cv. Hysun-33, sown in single rows 70 em apart. Treatments in the experiment were control (weedy check), gramoxone (paraquat) @ 3 lit ha' as directed post-emergence, Dual 500 E.C. (metolachlor) @ 3 lit ha' as pre-plant incorporated, Sonalon (ethalfluralin) @ 3.75 lit and 5 lit ha' pre-plant incorporated. The results revealed that ethalfluralin was the most effective herbicide in controlling weeds and improving sunflower yield of seed oil contents significantly.